Bridging the gap between classical and contemporary vocal technique: implications for the choral rehearsal. Issue 1 (2nd January 2017) - Winnie, Brian J.
Abstract: Within the traditional choral canon, choral teachers are expected to teach authentic performance practice that incorporates changes in vocal production among varying genres and style periods from Renaissance to Contemporary. Contemporary commercial music (CCM) requires a different vocal approach than the standard Western classical tradition, yet most singing teachers are not being trained in vocal technique associated with CCM in traditional university music departments. Since choral singers are asked to create a variety of vocal qualities and switch between those qualities within a single performance, this article argues that singing teachers should be trained to utilize a multifaceted approach to developing vocal technique, given that recent singing pedagogy literature implies that there is a significant lack of training in the areas of CCM. The scope of this article is to discuss the main tenets of breath, onset, and resonance inherent in both bel canto and contemporary vocal technique by examining both vocal science and traditional vocal pedagogy. By developing a pathway between these styles, teachers enhance their teaching of diverse repertoire without having to learn an entirely new pedagogy. From changes within these three tenets, numerous vocal qualities can be created that are sustainable and healthy for all singers.